High-temperature-resistant low-impedance electrolyte, battery and energy storage equipment
By introducing compounds with the structure of Formula I and Formula II into the electrolyte, an interface film with high ionic conductivity is formed, which solves the problem that the positive and negative electrode films are easy to decompose and have large impedance in high-temperature environments of traditional electrolytes, and significantly improves the cycle stability and high-temperature performance of the battery.
Patent Information
- Application Number
- CN202411901517.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-18
AI Technical Summary
When traditional electrolytes operate in high-temperature environments, the positive and negative electrode films are easy to decompose and have a large impedance, resulting in reduced battery performance and safety hazards.
Compounds with structures of Formula I and structures of Formula II are introduced into the electrolyte, and the interface film with high ion conductivity is formed on the surface of the positive and negative electrodes, which inhibit the dissolution of transition metal ions and slow down the gas production in high-temperature cycles.
The cycle stability and performance of the battery are significantly improved, especially the cycle capability in high-temperature environments, and the impedance of the battery is reduced.
Smart Images

Figure CN119650858A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and in particular relates to a high temperature resistant low impedance electrolyte, a battery and an energy storage device. Background Art
[0002] With the continuous advancement of science and technology and the increasing demand for energy in society, batteries play an increasingly indispensable role in modern life. Whether in consumer electronics, transportation, or renewable energy storage, battery performance and stability are key considerations. Among the many components of these batteries, the electrolyte is one of its core components and has a vital impact on the overall performance of the battery. The electrolyte is not only responsible for the conduction of ions between the positive and negative electrodes of the battery, but also directly affects the cycle stability and life of the battery.
[0003] Electrolyte additives are one of the most important components in the electrolyte. By regulating the composition of the electrode surface film, these additives can significantly improve the stability of the battery interface. During the operation of the battery, a protective film will form on the surface of the positive and negative electrodes. The quality and stability of this film directly affect the performance of the battery. Under high temperature conditions, some unstable chemical components in the electrode surface film may decompose. This decomposition will cause the solvent, salt and other components in the electrolyte to react rapidly, produce gas and damage the integrity of the battery structure.
[0004] In addition, high temperature conditions tend to exacerbate unnecessary side reactions inside the battery, which not only consume the active materials in the battery, but may also cause the electrode surface film to continue to thicken. This thickening will increase the resistance of the battery, thereby affecting the battery's charging speed and energy efficiency, and may even cause battery overheating and safety hazards. Therefore, how to design an interfacial film that can remain stable at high temperatures and effectively protect the electrode has become a key challenge in the design of electrolyte additives. Summary of the invention
[0005] In order to solve the problems of the prior art, the present invention provides a high-temperature resistant and low-impedance electrolyte. By introducing compounds of formula I and formula II into the electrolyte, the problem that the positive and negative electrode films generated by traditional electrolytes when operating in a high-temperature environment are easy to decompose and have high impedance is solved, thereby obtaining a high-temperature resistant and low-impedance electrolyte.
[0006] In the first aspect, the present invention provides a high temperature resistant low impedance electrolyte, including an electrolyte salt, a non-aqueous organic solvent and a first additive, wherein the first additive is one or more compounds having a structure of Formula I and a structure of Formula II:
[0007]
[0008] Among them, R1~R7 are independently selected from any one of hydrogen, halogen, cyano, substituted or unsubstituted alkyl with 1-8 carbon atoms, aryl with 6-8 carbon atoms and sulfonyl with 1-8 carbon atoms. When substituted, the substituent is selected from any one of halogen, cyano, C1-C6 alkyl, amino, nitro, hydroxyl, carboxyl and aldehyde. Q is selected from any one of Na or Li.
[0009] As some preferred schemes, in the compounds having the structures of Formula I and Formula II, R1 is selected from any one of hydrogen, halogen, substituted or unsubstituted alkyl with 1-6 carbon atoms and sulfonyl with 1-6 carbon atoms, and when substituted, the substituent is selected from cyano; R2-R6 are independently selected from any one of hydrogen, halogen, substituted or unsubstituted alkyl with 1-6 carbon atoms, and when substituted, the substituent is selected from halogen and cyano; R7 is selected from any one of substituted or unsubstituted alkyl with 1-6 carbon atoms, and when substituted, the substituent is selected from halogen and cyano, and Q is selected from any one of Na or Li.
[0010] As some preferred schemes, in the compounds having the structures of Formula I and Formula II, R1 is selected from any one of hydrogen, an alkyl group with 1-4 carbon atoms substituted by a cyano group, and a sulfonyl group with 1-4 carbon atoms, at least one of R2-R6 is selected from any one of an alkyl group with 1-4 carbon atoms substituted by a cyano group; R7 is selected from an alkyl group with 1-4 carbon atoms substituted or unsubstituted by a cyano group, and Q is selected from any one of Na or Li.
[0011] As a further solution, the content of the compound having the structure of formula I in the electrolyte is selected from 0.1 to 5 wt %, and the content of the compound having the structure of formula II in the electrolyte is selected from 0.1 to 5 wt %.
[0012] As some preferred solutions, the content of the compound having the structure of formula I in the electrolyte is selected from 0.3 to 2 wt%, and the content of the compound having the structure of formula II in the electrolyte is selected from 0.2 to 2 wt%;
[0013] As some preferred solutions, the total content of the compounds having the structure of Formula I and the structure of Formula II in the electrolyte is selected from 0.3wt% to 1.5wt%.
[0014] As some preferred solutions, the total content of the compounds having the structure of Formula I and the structure of Formula II in the electrolyte is selected from 0.5wt% to 1.5wt%.
[0015] As a further embodiment, the concentration of the electrolyte salt in the electrolyte is selected from 0.5 mol / L to 2 mol / L.
[0016] The electrolyte salt is selected from any one of lithium salt and sodium salt.
[0017] The lithium salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorophosphate, and lithium difluorobis(oxalatophosphate).
[0018] As a further embodiment, the sodium salt is selected from one or more of sodium hexafluorophosphate, sodium tetrafluoroborate, sodium hexafluoroarsenate, sodium difluorophosphate, sodium difluorobis(trifluoromethylsulfonyl)imide, sodium trifluoromethanesulfonate, and sodium bis(trifluoromethylsulfonyl)imide.
[0019] As a further solution, the non-aqueous solvent is selected from carbonate solvents and carboxylate solvents, wherein the mass proportion of carbonate solvents in the electrolyte is selected from 20 to 80 wt %, and the mass proportion of carboxylate solvents in the electrolyte is selected from 30 to 50 wt %.
[0020] As some preferred solutions, the mass proportion of the carbonate solvent in the electrolyte is selected from 30 to 70 wt %, and the mass proportion of the carboxylate solvent in the electrolyte is selected from 30 to 40 wt %.
[0021] As a further solution, the carbonate solvent is selected from a mixture of one or more of cyclic carbonates and linear carbonates.
[0022] As a further solution, the carboxylate solvent is selected from one or a mixture of acetate solvents, propionate solvents, and butyrate solvents.
[0023] As a further solution, the high temperature resistant low impedance electrolyte may further include a second additive, wherein the second additive is selected from any one of sulfite additives, sulfonate additives, carbonate additives, and sulfate additives, or a mixture of several of them.
[0024] As a further solution, in the high temperature resistant low impedance electrolyte, the total mass proportion of the second additive in the electrolyte is selected from 0.2 to 5 wt %.
[0025] In a second aspect, the present solution also provides a battery comprising the high temperature resistant and low impedance electrolyte proposed in the present solution.
[0026] As a further solution, the battery is selected from any one of a lithium ion battery and a sodium ion battery.
[0027] As a further solution, the battery further includes a positive electrode, and the positive electrode includes a positive electrode material layer and a positive electrode current collector.
[0028] As a further solution, the positive electrode material layer includes a positive electrode active material, a positive electrode binder and a positive electrode conductor.
[0029] As a further solution, the positive electrode active material is selected from one or more of sodium copper iron manganate, sodium nickel iron manganate, sodium vanadium phosphate, sodium fluorovanadium phosphate, sodium iron pyrophosphate, sodium iron sulfate, and modified sodium ferrocyanide.
[0030] As a further solution, the positive electrode binder is selected from at least one of thermoplastic resin, acrylic resin, sodium carboxymethyl cellulose and styrene butadiene rubber.
[0031] As a further solution, the battery also includes a negative electrode.
[0032] As a further solution, the negative electrode includes a negative electrode sheet and a negative electrode current collector;
[0033] As a further solution, the negative electrode sheet includes a negative electrode active material, a negative electrode binder and a negative electrode conductor.
[0034] Preferably, the negative electrode active material is selected from at least one of soft carbon, hard carbon, sodium titanate, metallic sodium, carbon nanotubes, carbon black, carbon aerogel, graphite and graphene.
[0035] As a further solution, the battery further includes a separator.
[0036] Compared with the prior art, the present invention has at least the following beneficial effects:
[0037] The present invention provides a high temperature resistant and low impedance electrolyte, which can effectively form a high ionic conductivity film containing nitrogen and silicon during the battery cycle by introducing a compound having a structure of formula I, and significantly improve the ionic conductivity. In addition, the trimethylsilyl group in the structure of formula I can react with active protons in water and acid to achieve the effect of removing water and acid, and enhance the interface stability between the electrode and the electrolyte at high temperature. Secondly, the compound having the structure of formula II forms an interface film with high ionic conductivity on the surface of the positive electrode through its sulfonamide group, inhibits the dissolution of transition metal ions and slows down the gas production phenomenon in high temperature cycles. At the same time, the reaction of the isoxazole group and the sulfonamide group on the surface of the negative electrode synergistically generates an interface film rich in nitrogen and sulfur, further reducing the battery impedance. The two compounds produce a synergistic effect, especially the phenyl group in the structure of formula II can produce an electronic effect with the oxazolidinone ring of the structure of formula I, optimize the electron distribution, and further reduce the interface impedance after the film. Therefore, the present invention significantly improves the cycle stability and performance of the battery, especially the cycle capacity in a high temperature environment. DETAILED DESCRIPTION
[0038] For ease of understanding, the present invention will be described in more detail below and examples of the present invention are given, but the scope of the present invention is not limited thereby.
[0039] In a first aspect, the present invention provides a high temperature resistant low impedance electrolyte, comprising an electrolyte salt, a non-aqueous organic solvent and a first additive, wherein the first additive is one or more compounds having a structure of Formula I and a structure of Formula II:
[0040]
[0041] Among them, R1~R7 are independently selected from any one of hydrogen, halogen, cyano, substituted or unsubstituted alkyl with 1-8 carbon atoms, aryl with 6-8 carbon atoms and sulfonyl with 1-8 carbon atoms. When substituted, the substituent is selected from any one of halogen, cyano, C1-C6 alkyl, amino, nitro, hydroxyl, carboxyl and aldehyde. Q is selected from any one of Na or Li.
[0042] In the electrolyte, we first introduced a compound with the structure of Formula I. For the compound with the structure of Formula I, the Si-N bond is easily broken during the battery cycle and forms a film on the surface of the positive and negative electrodes, thereby introducing high ionic conductivity components containing nitrogen and silicon into the surface films of the positive and negative electrodes to improve the ionic conductivity. At the same time, the trimethylsilyl group can react with the active protons in water and acid, thereby achieving the purpose of removing water and acid, and improving the interface stability between the electrode and the electrolyte under high temperature conditions. On this basis, we further introduced compounds with the structure of formula II. First, the presence of the sulfonamide group in the compound with the structure of formula II enables it to oxidize on the surface of the positive electrode to form an interfacial film with high ionic conductivity, while inhibiting the dissolution of transition metal ions and high-temperature cyclic gas production during the cycle. Secondly, the isoxazole group can generate an interfacial film rich in multiple components such as nitrogen and sulfur on the surface of the negative electrode, further reducing the battery impedance and improving the cycle stability. More interestingly, we believe that the presence of the phenyl group in the compound with the structure of formula II enables it to produce an electronic effect with the oxazolidinone ring in the compound with the structure of formula I through its unique conjugated π electron system, thereby optimizing the electron distribution and further reducing the interfacial impedance after film formation. Under the joint action of the compounds with the structures of formula I and formula II, we have optimized the ionic conductivity and reduced the interfacial impedance while improving the battery cycle stability, and obtained a high-temperature resistant and low-impedance electrolyte.
[0043] As some preferred schemes, in the compounds having the structures of Formula I and Formula II, R1 is selected from any one of hydrogen, halogen, substituted or unsubstituted alkyl with 1-6 carbon atoms and sulfonyl with 1-6 carbon atoms, and when substituted, the substituent is selected from cyano; R2-R6 are independently selected from any one of hydrogen, halogen, substituted or unsubstituted alkyl with 1-6 carbon atoms, and when substituted, the substituent is selected from halogen and cyano; R7 is selected from any one of substituted or unsubstituted alkyl with 1-6 carbon atoms, and when substituted, the substituent is selected from halogen and cyano, and Q is selected from any one of Na or Li.
[0044] Different R1~R7 functional groups will have different effects on the performance. In the electrolyte, the presence of aromatic groups helps to optimize the electron configuration with the compound having structural formula II, while the sulfonyl group can further form an interface film with high ionic conductivity on the surface of the positive and negative electrodes. In addition, when replaced by cyano groups, the presence of cyano groups can inhibit the dissolution of transition metals, thereby giving the battery better high-temperature cycle capacity retention and room-temperature cycle capacity retention.
[0045] As some preferred schemes, in the compounds having the structures of Formula I and Formula II, R1 is selected from any one of hydrogen, an alkyl group having 1 to 4 carbon atoms substituted by a cyano group, and a sulfonyl group having 1 to 4 carbon atoms. At least one of R2 to R6 is selected from any one of an alkyl group having 1 to 4 carbon atoms substituted by a cyano group; R7 is selected from an alkyl group having 1 to 4 carbon atoms substituted or unsubstituted by a cyano group, and Q is selected from any one of Na or Li.
[0046] As some exemplary schemes, the compound having the structure of formula I is selected from Any one of .
[0047] As some exemplary schemes, the compound having the structure of formula II is selected from Any one of .
[0048] As a further solution, the content of the compound having the structure of formula I in the electrolyte is selected from 0.1 to 5 wt%, and the content of the compound having the structure of formula II in the electrolyte is selected from 0.1 to 5 wt%. Although the addition of the compounds having the structures of formula I and formula II can form an interface film with good high temperature stability and low impedance, it is still necessary to pay attention to the ratio between the addition amount and the electrolyte, so as to better play the effect of the compounds having the structures of formula I and formula II. When the content of the compound having the structure of formula I in the electrolyte is selected from 0.1 to 5 wt%, and the content of the compound having the structure of formula II in the electrolyte is selected from 0.1 to 5 wt%, on the one hand, the generation of a high temperature resistant and low impedance interface film can be guaranteed, and on the other hand, the interface impedance can be further optimized, thereby effectively improving the cycle capacity retention rate of the battery at normal and high temperatures.
[0049] As some preferred solutions, the content of the compound having the structure of formula I in the electrolyte is selected from 0.3-2 wt %, and the content of the compound having the structure of formula II in the electrolyte is selected from 0.2-2 wt %.
[0050] As some preferred schemes, the total content of the compounds having the structure of formula I and the structure of formula II in the electrolyte is selected from 0.3wt% to 1.5wt%, and the content of the compound having the structure of formula II in the electrolyte is selected from 0.3wt% to 1.5wt%, which helps to form a more stable high temperature resistant, low impedance interface film, while further optimizing the interface impedance and improving the battery cycle performance.
[0051] As some preferred solutions, the total content of the compounds having the structure of Formula I and the structure of Formula II in the electrolyte is selected from 0.5wt% to 1.5wt%.
[0052] As a further embodiment, the concentration of the electrolyte salt in the electrolyte is selected from 0.5 mol / L to 2 mol / L.
[0053] As a further solution, the electrolyte salt is selected from any one of lithium salt and sodium salt;
[0054] The lithium salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorophosphate, and lithium difluorobis(oxalatophosphate).
[0055] As a further embodiment, the sodium salt is selected from one or more of sodium hexafluorophosphate, sodium tetrafluoroborate, sodium hexafluoroarsenate, sodium difluorophosphate, sodium difluorobis(trifluoromethylsulfonyl)imide, sodium trifluoromethanesulfonate, and sodium bis(trifluoromethylsulfonyl)imide.
[0056] As a further solution, the non-aqueous solvent is selected from carbonate solvents and carboxylate solvents, wherein the mass proportion of carbonate solvents in the electrolyte is selected from 20 to 80 wt %, and the mass proportion of carboxylate solvents in the electrolyte is selected from 30 to 50 wt %.
[0057] As some preferred solutions, the mass proportion of the carbonate solvent in the electrolyte is selected from 30 to 70 wt %, and the mass proportion of the carboxylate solvent in the electrolyte is selected from 30 to 40 wt %.
[0058] As a further solution, the carbonate solvent is selected from a mixture of one or more of cyclic carbonates and linear carbonates.
[0059] As a further embodiment, the cyclic carbonate solvent is selected from the group consisting of vinylene carbonate, ethylene carbonate, propylene carbonate, butylene carbonate, methyl vinyl carbonate, methyl propylene carbonate, fluoroethylene carbonate, fluoropropylene carbonate, bis(fluoromethyl) carbonate, difluoroethylene carbonate, vinyl carbonate, fluoroethylene carbonate, γ-butyrolactone, or a mixture of one or more thereof.
[0060] As a further embodiment, the linear carbonate solvent is selected from one or a mixture of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propyl methyl carbonate, methyl isobutyl carbonate, dipropyl carbonate, methyl propyl carbonate, dibutyl carbonate, ethyl propyl carbonate, and methyl tert-butyl carbonate.
[0061] As a further solution, the carboxylate solvent is selected from one or a mixture of acetate solvents, propionate solvents, and butyrate solvents.
[0062] As a further embodiment, the acetate solvent is selected from one or a mixture of methyl acetate, ethyl acetate, propyl acetate, butyl acetate, isobutyl acetate, amyl acetate, isoamyl acetate, hexyl acetate, benzyl acetate, cyclohexyl acetate, and n-propyl acetate.
[0063] As a further solution, the propionate solvent is selected from one or a mixture of isopropyl isobutyrate, butyl propionate, isobutyl propionate, ethyl propionate, propyl propionate, and butyl propionate.
[0064] As a further solution, the butyrate solvent is selected from one or a mixture of methyl butyrate, ethyl butyrate, propyl butyrate, butyl butyrate, isobutyl butyrate, and ethyl n-butyrate.
[0065] As a further solution, the high temperature resistant low impedance electrolyte may further include a second additive, wherein the second additive is selected from any one of sulfite additives, sulfonate additives, carbonate additives, and sulfate additives, or a mixture of several of them.
[0066] As a further solution, the sulfite additive is selected from any one of ethylene sulfite and propylene sulfite or a mixture of several of them.
[0067] As a further embodiment, the sulfonate additive is selected from any one of 1,3-propane sultone, 1,4-butane sultone, and 1,3-propene sultone, or a mixture of several of them.
[0068] As a further solution, the carbonate additive is selected from any one or more of vinylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, and diphenyl carbonate.
[0069] As a further embodiment, the sulfate ester additive is selected from vinyl sulfate.
[0070] As a further solution, in the high temperature resistant low impedance electrolyte, the total mass proportion of the second additive in the electrolyte is selected from 0.2 to 5 wt %.
[0071] In a second aspect, the present solution also provides a battery comprising the high temperature resistant and low impedance electrolyte proposed in the present solution.
[0072] As a further solution, the battery is selected from any one of a lithium ion battery and a sodium ion battery.
[0073] As a further solution, the battery further includes a positive electrode, and the positive electrode includes a positive electrode material layer and a positive electrode current collector.
[0074] As a further solution, the positive electrode material layer includes a positive electrode active material, a positive electrode binder and a positive electrode conductor.
[0075] As a further solution, the positive electrode active material is selected from one or more of sodium copper iron manganate, sodium nickel iron manganate, sodium vanadium phosphate, sodium fluorovanadium phosphate, sodium iron pyrophosphate, sodium iron sulfate, and modified sodium ferrocyanide.
[0076] As a further solution, the positive electrode binder is selected from at least one of thermoplastic resin and acrylic resin.
[0077] As a further embodiment, the thermoplastic resin includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of tetrafluoroethylene-perfluoroalkyl vinyl ether, a copolymer of ethylene-tetrafluoroethylene, a copolymer of vinylidene fluoride-tetrafluoroethylene, a copolymer of vinylidene fluoride-trifluoroethylene, a copolymer of vinylidene fluoride-chlorotrifluoroethylene, a copolymer of vinylidene fluoride-fluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, a thermoplastic polyimide, polyethylene and polypropylene.
[0078] As a further solution, the acrylic resin includes at least one of vinyl acrylate resin, methyl acrylate resin, butyl acrylate resin, acrylic styrene resin, acrylate resin, acrylate copolymer resin, acrylic resin, and acrylic emulsion resin.
[0079] As a further solution, the positive electrode conductive agent includes at least one of conductive graphite, carbon nanotubes, graphene, reduced graphene oxide, conductive carbon black, conductive carbon balls, and conductive carbon fibers.
[0080] As a further solution, the battery also includes a negative electrode.
[0081] As a further solution, the negative electrode includes a negative electrode sheet and a negative electrode current collector.
[0082] As a further solution, the negative electrode current collector is not limited in principle. As some exemplary solutions, the negative electrode current collector can be selected from any one of aluminum foil, copper foil, and stainless steel.
[0083] As a further solution, the negative electrode sheet includes a negative electrode active material, a negative electrode binder and a negative electrode conductor.
[0084] As a further solution, the negative electrode active material is selected from at least one of soft carbon, hard carbon, sodium titanate, metallic sodium, carbon nanotubes, carbon black, carbon aerogel, graphite, and graphene.
[0085] As a further solution, the type of the negative electrode binder is not limited, and technicians can choose it according to actual needs, including at least one of styrene butadiene rubber (SBR), styrene-butadiene rubber, water-based acrylic resin and carboxymethyl cellulose (CMC).
[0086] As a further solution, the negative electrode conductive agent is selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, conductive carbon black and carbon nanofibers.
[0087] As a further solution, the battery further includes a separator.
[0088] As a further solution, the type of the diaphragm is not limited, and technicians can choose according to actual needs.
[0089] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application and do not represent all possible embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0090] The chemical raw materials involved in the following examples and comparative examples are all prior art and are commercially available. The experimental devices, test devices, etc. involved in the following examples and comparative examples are all conventional devices in the art, without special requirements and limitations.
[0091] Take sodium-ion batteries as an example:
[0092] Example 1
[0093] Synthesis of (Compound II-1, the first substance having the structure of Formula II)
[0094] Using 4-(trifluoromethyl)benzenesulfonyl chloride (CAS No.: 2991-42-6) and 3-amino-5-methylisoxazole (CAS No.: 1072-67-9) as raw materials, a sulfonamide intermediate is obtained by sulfonylation reaction, and then the intermediate is reacted with an ethanol solution of sodium hydroxide to obtain compound II-1.
[0095]
[0096] Preparation of electrolyte
[0097] In an inert atmosphere glove box where the H2O and O2 contents are both less than 0.1ppm, ethylene carbonate, propylene carbonate, diethyl carbonate and propyl propionate are thoroughly mixed in a ratio of 2:3:2:3, and then 0.9mol / L sodium hexafluorophosphate and 0.1mol / L sodium bis(fluorosulfonyl)imide are added. After sufficient dissolution, 0.3wt% 3-trimethylsilyl-2-oxazolidinone (Compound I-1, the first substance having the structure of Formula I, CAS No.: 43112-38-5) and 0.2wt% Compound II-1 are added.
[0098] Preparation of batteries
[0099] The battery was prepared using sodium copper iron manganese oxide as the positive electrode material, hard carbon as the negative electrode material, and a polyethylene-based separator as the separator.
[0100] Example 2
[0101] The preparation method is the same as that of Example 1, except that the mass proportion of compound II-1 in the electrolyte is 0.1 wt %.
[0102] Example 3
[0103] The preparation method is the same as that of Example 1, except that the mass percentage of compound II-1 in the electrolyte is 0.5 wt %.
[0104] Example 4
[0105] The preparation method is the same as that of Example 1, except that the mass proportion of compound I-1 in the electrolyte is 0.5 wt %.
[0106] Example 5
[0107] The preparation method is the same as that of Example 1, except that the mass percentage of compound I-1 in the electrolyte is 1 wt %.
[0108] Example 6
[0109] The preparation method is the same as in Example 1, except that compound I-1 is replaced by compound I-2
[0110] Example 7
[0111] The preparation method is the same as in Example 1, except that compound I-1 is replaced by compound I-3
[0112] Example 8
[0113] The preparation method is the same as in Example 1, except that compound II-1 is replaced by compound II-2
[0114]
[0115] Example 9
[0116] The preparation method is the same as in Example 1, except that compound II-1 is replaced by compound II-3
[0117]
[0118] Example 10
[0119] The preparation method is the same as that of Example 1, except that 0.5 wt % of 1,3-propane sultone is additionally added.
[0120] Comparative Example 1
[0121] The preparation method is the same as that of Example 1, except that compound I-1 and compound II-1 are not added.
[0122] Comparative Example 2
[0123] The preparation method is the same as that of Example 1, except that compound II-1 is not added.
[0124] Comparative Example 3
[0125] The preparation method is the same as that of Example 1, except that compound I-1 is not added.
[0126] Comparative Example 4
[0127] The preparation method is the same as that of Example 1, except that 3-methyl-2-oxazolidinone is used to replace compound I-1.
[0128] Comparative Example 5
[0129] The preparation method is the same as that of Example 1, except that N,N-dimethylbenzenesulfonamide is used to replace compound II-1.
[0130] Comparative Example 6
[0131] The preparation method is the same as that of Example 1, except that the mass proportion of Compound II-1 in the electrolyte is 10 wt %.
[0132] Comparative Example 7
[0133] The preparation method is the same as that of Example 1, except that the mass proportion of compound I-1 in the electrolyte is 10 wt %.
[0134] The preparation conditions of Examples 1-10 and Comparative Examples 1-7 are shown in Table 1.
[0135] Test Method
[0136] Normal temperature cycle test: Place the sodium ion battery in a 25°C environment, charge it to 4.0V at 1C constant current and constant voltage, then discharge it to 1.5V at 1C constant current, and calculate the capacity retention rate based on the discharge capacity of the first cycle.
[0137] Capacity retention rate after 500 cycles at room temperature = (discharge capacity at the 500th cycle at room temperature / discharge capacity at the 1st cycle at room temperature)*100%.
[0138] High temperature test: The sodium ion battery is placed in a 60°C environment, charged to 4.0V at 1C constant current and constant voltage, and then discharged to 1.5V at 1C constant current. The capacity retention rate is calculated based on the discharge capacity of the first cycle.
[0139] High-temperature cycle 500-cycle capacity retention rate % = (high-temperature 500th cycle discharge capacity / high-temperature 1st cycle discharge capacity) * 100%.
[0140] The test results are shown in Table 2.
[0141] Table 1
[0142]
[0143]
[0144] Table 2
[0145] Capacity retention rate after 500 cycles at room temperature (%) Capacity retention rate after 500 cycles of high temperature cycling (%) Example 1 96.56 93.82 Example 2 95.81 92.64 Example 3 96.87 94.35 Example 4 96.91 94.12 Example 5 97.36 94.62 Example 6 95.48 91.74 Example 7 96.35 94.16 Example 8 96.14 94.35 Example 9 94.36 94.62 Example 10 94.21 94.15 Comparative Example 1 32.91 28.16 Comparative Example 2 65.54 43.72 Comparative Example 3 61.75 51.39 Comparative Example 4 63.17 53.64 Comparative Example 5 72.61 60.35 Comparative Example 6 - - Comparative Example 7 58.19 63.94
[0146] It can be observed from Examples 1-10 and Comparative Examples 1-7 that Example 1-10 as a whole exhibits higher room temperature cycle capacity retention rate and high temperature cycle capacity retention rate than Comparative Examples 1-7. Whether at room temperature or at high temperature, Example 1-10 exhibits excellent cycle capacity retention rate, indicating that the addition of high temperature resistant and low impedance electrolyte can effectively improve the stability of the battery at high temperature, while reducing the battery impedance and improving the cycle performance of the battery at high and room temperatures.
[0147] From Example 1 and Comparative Example 1, it can be observed that when the compounds having the structures of Formula I and Formula II are not added, after 500 cycles of Comparative Example 1, the normal temperature cycle capacity retention rate is only 32.91%, and the high temperature cycle capacity retention rate is only 28.16%, which are much lower than the results of Example 1. This shows that the addition of compounds having the structures of Formula I and Formula II is of great significance for improving the battery cycle capacity and reducing the battery impedance.
[0148] Secondly, it can be observed from Example 1, Comparative Examples 2 and 3 that no matter which of the compounds with structures of Formula I and Formula II is missing, the battery cycle capacity may be seriously affected. This may be because in the high temperature resistant low impedance electrolyte, the compound with structure of Formula I can introduce Si-N bonds to form films on the surfaces of the positive and negative electrodes, and use trimethylsilyl to remove water and acid, while the compound with structure of Formula II can also use isoxazole groups and sulfonamide groups to form films, and inhibit the dissolution of transition metal ions and high temperature cycle gas production during the cycle, and reduce the battery impedance. More importantly, adding compounds with structures of Formula I and Formula II at the same time can also use the oxazolidinone ring in the compound with structure of Formula I and the phenyl in the compound with structure of Formula II to cooperate with each other, thereby optimizing the electron distribution and further reducing the interface impedance. When only one electrolyte is added to the high temperature resistant low impedance electrolyte, the compounding effect cannot be fully exerted. Therefore, Comparative Examples 2-3 show worse room temperature and high temperature cycle performance than Example 1.
[0149] Example 1, Comparative Examples 4-5 further discuss the compounding effect of compounds having the structure of Formula I and Formula II. It can be observed from Comparative Examples 4-5 that when 3-methyl-2-oxazolidinone and N,N-dimethylbenzenesulfonamide are used to replace Compound I-1 and Compound II-1, after 500 cycles of Comparative Example 4, the cycle capacity retention rates at room temperature and high temperature are 62.17% and 50.64%, respectively. The room temperature cycle capacity retention rate and high temperature cycle capacity retention rate of Comparative Example 5 are 72.61% and 60.35%, respectively. It is worth noting that Comparative Example 5 shows a higher cycle capacity retention ability than Comparative Example 2, which may be due to the fact that the N,N-dimethylbenzenesulfonamide used as a replacement also has the structure of sulfonyl and phenyl groups, so it can still play a certain synergistic role with Compound I-1, but due to the lack of isoxazole groups, the performance is weaker than that of Example 1. The performance of Comparative Example 4 is slightly better than that of Comparative Example 3, indicating that the oxazolidinone ring has the effect of reducing internal resistance, but the effect is not as good as that of Compound I-1, so the performance is much weaker than that of Example 1.
[0150] Example 1, Comparative Examples 6 and 7 further discuss the effect of the content of compounds having the structures of Formula I and Formula II in the electrolyte on the cycle performance. It can be observed that no matter which of the compounds having the structures of Formula I and Formula II accounts for more than 5wt% of the mass in the electrolyte, it may affect the cycle stability performance of the battery. When the mass proportion of compound II-1 in Comparative Example 6 is 10wt%, Comparative Example 6 even appears to be insoluble and difficult to test. When the mass proportion of compound I-1 is 10wt% (Comparative Example 7), after 500 cycles, the high-temperature cycle capacity retention rate is only 63.94%, and the room temperature cycle capacity retention rate is only 58.19%, both of which are lower than Example 1, indicating that excessive amounts of compounds having the structures of Formula I and Formula II may in turn affect the performance of the battery. Therefore, it is necessary to control the content of the compound having the structure of Formula I in the electrolyte to be selected from 0.1 to 5wt%, and the content of the compound having the structure of Formula II in the electrolyte to be selected from 0.1 to 5wt%.
[0151] Examples 1-5 further discuss the effect of the content of the compound having the structure of Formula II in the high temperature resistant low impedance electrolyte on its cycle performance. It can be observed that, on the basis of the content of the compound having the structure of Formula I in the electrolyte being selected from 0.1 to 5wt%, and the content of the compound having the structure of Formula II in the electrolyte being selected from 0.1 to 5wt%, when the total content of the additive having the structure of Formula I and the compound having the structure of Formula II in the electrolyte is controlled to be selected from 0.3 to 1.5wt%, it helps to further regulate the stability and interface impedance of the interface film formed in the high temperature resistant low impedance electrolyte, obtain an interface film with stronger stability and lower interface impedance, thereby optimizing the battery cycle performance.
[0152] Examples 1, 6, and 7 further discuss the effect of the structure of the compound having the structure of Formula I on the battery cycle performance. It can be observed from Examples 1 and 7 and Example 6 that when R1 is selected from any one of hydrogen, halogen, substituted or unsubstituted alkyl with 1-6 carbon atoms, aryl, and sulfonyl, and when substituted, the substituent is selected from halogen and cyano, Examples 1, 6, and 7 all exhibit excellent room temperature cycle capacity retention rates, but Examples 1 and 7 exhibit better high temperature cycle capacity retention rates than Example 6, which may be because the presence of trifluoromethyl may be more conducive to improving low temperature performance, but cyano or hydrogen, halogen has better cycle capacity retention rates at high temperatures; further, it can be further observed from the comparison of Examples 1 and 7 that Example 1 exhibits a better room temperature cycle capacity retention rate than Example 7, while Example 7 exhibits a better high temperature cycle capacity retention rate than Example 1, which may be because the presence of cyano can inhibit the dissolution of transition metals, but while protecting the positive electrode, it will increase the interface impedance, so Example 1 has a better room temperature cycle capacity retention rate, while Example 7 exhibits a better high temperature cycle capacity retention rate.
[0153] Examples 1, 8, and 9 discuss the effects of different conditions of R2-R7 in the compound having the structure of Formula II on the performance of the electrolyte. It can be observed from Examples 1, 8, and 9 that the room temperature cycle capacity retention rates of Examples 1 and 8 are better than those of Example 9, while the high temperature cycle capacity retention rate of Example 9 is better than that of Examples 1 and 8. This may be because the sulfonamide group can form an interface film with high ionic conductivity on the positive electrode surface, while inhibiting the dissolution of transition metal ions and the occurrence of high temperature cycle gas generation during the cycle. However, the impedance after film formation is higher than that of Examples 1 and 8. Therefore, the high temperature performance of Example 9 is better than that of Examples 1 and 8. As for Examples 1 and 8, firstly, compared with Example 9, R7 of Examples 1 and 8 is substituted by an alkyl group. At the same time, compared with Example 1, Example 7 shows higher room temperature cycle capacity retention rate and high temperature cycle capacity retention rate than Example 1. This may be because R2-R6 in Example 7 are substituted by cyano groups, and at the same time, R7 is replaced by an alkyl group. These two groups can effectively improve the room temperature cycle capacity retention rate of the battery, and the cyano group can further optimize the inhibition of transition metal dissolution. Therefore, Example 8 shows better room temperature cycle capacity retention rate and high temperature cycle capacity retention rate than Example 1.
[0154] The effect of the second additive in Examples 1 and 10 can be observed from Examples 1 and 10 that Example 10, in which 1,3-propane sultone is additionally added as the second additive, exhibits a room temperature cycle capacity retention rate and a high temperature cycle capacity retention rate that are significantly better than those in Example 1, indicating that the addition of the second additive helps to further optimize the electrolyte effect and improve the high temperature cycle energy and room temperature cycle capacity of the battery.
[0155] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. Although the embodiments of the present invention have been shown and described above, it can be understood that the above-described embodiments are exemplary and cannot be understood as limitations of the present invention. Those of ordinary skill in the art can change, modify, replace and deform the above-described embodiments within the scope of the present invention. In addition, those of ordinary skill in the art can combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.
Claims
1. A high temperature resistant low impedance electrolyte, characterized in that: It includes an electrolyte salt, a non-aqueous organic solvent and a first additive, wherein the first additive is one or more compounds having a structure of Formula I and a structure of Formula II: Among them, R1~R7 are independently selected from any one of hydrogen, halogen, cyano, substituted or unsubstituted alkyl with 1-8 carbon atoms, aryl with 6-8 carbon atoms and sulfonyl with 1-8 carbon atoms. When substituted, the substituent is selected from any one of halogen, cyano, C1-C6 alkyl, amino, nitro, hydroxyl, carboxyl and aldehyde. Q is selected from any one of Na or Li.
2. The high temperature resistant low impedance electrolyte according to claim 1, characterized in that: In the compounds having the structures of Formula I and Formula II, R1 is selected from any one of hydrogen, halogen, substituted or unsubstituted alkyl with 1-6 carbon atoms and sulfonyl with 1-6 carbon atoms, and when substituted, the substituent is selected from cyano; R2-R6 are independently selected from any one of hydrogen, halogen, substituted or unsubstituted alkyl with 1-6 carbon atoms, and when substituted, the substituent is selected from halogen and cyano; R7 is selected from any one of substituted or unsubstituted alkyl with 1-6 carbon atoms, and when substituted, the substituent is selected from halogen and cyano, and Q is selected from any one of Na or Li.
3. The high temperature resistant low impedance electrolyte according to claim 1, characterized in that: In the compounds having the structures of Formula I and Formula II, R1 is selected from any one of hydrogen, an alkyl group having 1 to 4 carbon atoms substituted by a cyano group, and a sulfonyl group having 1 to 4 carbon atoms; at least one of R2-R6 is selected from any one of an alkyl group having 1 to 4 carbon atoms substituted by a cyano group; R7 is selected from an alkyl group having 1 to 4 carbon atoms substituted or unsubstituted by a cyano group; and Q is selected from any one of Na or Li.
4. The high temperature resistant low impedance electrolyte according to claim 1, characterized in that: The compound having the structure of formula I is selected from Any one of; The compound having the structure of formula II is selected from Any one of .
5. The high temperature resistant low impedance electrolyte according to claim 1, characterized in that: The content of the compound having the structure of formula I in the electrolyte is selected from 0.1 to 5 wt%, and the content of the compound having the structure of formula II in the electrolyte is selected from 0.1 to 5 wt%; Preferably, the content of the compound having the structure of formula I in the electrolyte is selected from 0.3 to 2 wt%, and the content of the compound having the structure of formula II in the electrolyte is selected from 0.2 to 2 wt%; Preferably, the total content of the compound having the structure of formula I and the structure of formula II in the electrolyte is selected from 0.3wt% to 1.5wt%; Preferably, the total content of the compounds having the structures of Formula I and Formula II in the electrolyte is selected from 0.5wt% to 1.5wt%.
6. The high temperature resistant low impedance electrolyte according to claim 1, characterized in that: The concentration of the electrolyte salt in the electrolyte is selected from 0.5 mol / L to 2 mol / L; The electrolyte salt is selected from any one of lithium salt and sodium salt; The lithium salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorophosphate, and lithium difluorobis(oxalatophosphate); The sodium salt is selected from one or more of sodium hexafluorophosphate, sodium tetrafluoroborate, sodium hexafluoroarsenate, sodium difluorophosphate, sodium difluorobis(trifluoromethylsulfonyl)imide, sodium trifluoromethanesulfonate, and sodium bis(trifluoromethylsulfonyl)imide; The non-aqueous solvent is selected from carbonate solvents and carboxylate solvents, wherein the carbonate solvent accounts for 20-80wt% of the electrolyte by weight, and the carboxylate solvent accounts for 30-50wt% of the electrolyte by weight; Preferably, the carbonate solvent accounts for 30-70 wt% of the electrolyte, and the carboxylate solvent accounts for 30-40 wt% of the electrolyte; Preferably, the carbonate solvent is selected from a mixture of one or more of cyclic carbonates and linear carbonates; Preferably, the carboxylate solvent is selected from one or a mixture of acetate solvents, propionate solvents and butyrate solvents.
7. The high temperature resistant low impedance electrolyte according to claim 1, characterized in that: The high temperature resistant low impedance electrolyte further comprises a second additive, wherein the second additive is selected from any one or a mixture of sulfite additives, sulfonate additives, carbonate additives, and sulfate additives; Preferably, in the high temperature resistant low impedance electrolyte, the total mass proportion of the second additive in the electrolyte is selected from 0.2 to 5 wt %.
8. A battery, characterized in that: The invention comprises the high temperature resistant and low impedance electrolyte as described in any one of claims 1 to 7, and the battery is selected from a lithium ion battery and a sodium ion battery.
9. The sodium ion battery according to claim 8, characterized in that: The sodium ion battery further comprises a positive electrode, wherein the positive electrode comprises a positive electrode material layer and a positive electrode current collector; Preferably, the positive electrode material layer comprises a positive electrode active material, a positive electrode binder and a positive electrode conductor; Preferably, the positive electrode active material is selected from one or more of sodium copper iron manganate, sodium nickel iron manganate, sodium vanadium phosphate, sodium fluorovanadium phosphate, sodium iron pyrophosphate, sodium iron sulfate, and modified sodium ferrocyanide; Preferably, the positive electrode binder is selected from at least one of a thermoplastic resin and an acrylic resin; The sodium ion battery also includes a negative electrode; Preferably, the negative electrode comprises a negative electrode sheet and a negative electrode current collector; Preferably, the negative electrode sheet comprises a negative electrode active material, a negative electrode binder and a negative electrode conductive agent; Preferably, the negative electrode active material is selected from at least one of soft carbon, hard carbon, sodium titanate, metallic sodium, carbon nanotubes, carbon black, carbon aerogel, graphite, and graphene; Preferably, the sodium ion battery also includes a separator.
10. An energy storage device, characterized in that: It comprises the high temperature resistant low impedance electrolyte according to any one of claims 1 to 7, the battery according to claim 8, or the sodium ion battery according to claim 9.